Evaluation and Characterization of Acute respiratory distress syndrome in tree shrews through TMT proteomic method - Junlong Xiong; Liji Zhang; Jinchao Xing; Weijian Huang; Ning Wang; Xiaoyan Lin; Shuhua He; Ming Liao; Jun He (PLoS ONE, 2025)
Acute respiratory distress syndrome (ARDS), a common cause of acute fatal respiratory, is characterized by severe inflammatory lung injury as well as hallmarks of increased pulmonary vascular permeability, neutrophil infiltration, and macrophage accumulation. Tree shrew, a squirrel-like small animal model, has been confirmed to have more similar traits to human ARDS with one-hit intratracheal instillation of LPS in our previous study. In this study, we characterized protein profile changes induced by intranasal LPS challenge in the tree shrew model through tandem mass tag (TMT)-based quantitative proteomics and type II alveolar epithelial cells through pathological analysis. In total, 4070 proteins (p <  0.05) were identified from lung tissues of the LPS-induced group and PBS group. Among the differential expression proteins (DEPs) detected by t-test (≥|1.5-fold|), 529 DEPs were identified, of which 304 were upregulated, and 225 were downregulated. The most important pathways involved in the process of ARDS had been identified by enrichment analysis: oxidative stress, apoptosis, inflammatory responses, and vascular endothelial injury. In addition, proteins have been reported in animal models or clinical patients also detail investigated for further analysis, such as ceruloplasmin (CP), hemopexin (HPX), sphingosine kinase 1 (SphK1), lactotransferrin (LTF), and myeloperoxidase (MPO) were upregulated in induced tissues and confirmed by western blot analysis. Overall, this study not only reveals a comprehensive proteomic analysis of the ARDS tree shrew model but also provides novel insights into multi-pathways responses induced by the LPS challenge of tree shrews. We highlight shared and unique proteomic changes in the lungs of ARDS tree shrews and identify novel pathways for acute lung injury, which may promote the model into basic research and translational research.